2016
DOI: 10.11113/.v78.7940
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Allergenic Proteins of Sea Snail (Cerithidea Obtusa) and Freshwater Snail (Pomacea Canaliculata)

Abstract: In Malaysian and certain Asian countries, snail has high market demand and popular to the local people as food. However, snail is also frequently reported as one of the worst food allergens, dominated by severe symptoms such as asthma and anaphylactic shock. Thus, the aims of this study is to determine the allergenicity of two species of edible snails; the local sea snail, Cerithidea obtusa and the freshwater snail Pomacea canaliculata. Snail extracts were prepared from the snail flesh and analyzed using sodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…This result also matched with the molecular mass of limpet, an aquatic snail found along seashores, with a wide molecular weight range of 15–250 kDa 5 . Our previous studies 11,12 also found almost similar results on fractionation of a protein mixture complex in the raw extract of C. obtusa , which expressed multiple protein bands between 12 and 250 kDa.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…This result also matched with the molecular mass of limpet, an aquatic snail found along seashores, with a wide molecular weight range of 15–250 kDa 5 . Our previous studies 11,12 also found almost similar results on fractionation of a protein mixture complex in the raw extract of C. obtusa , which expressed multiple protein bands between 12 and 250 kDa.…”
Section: Discussionsupporting
confidence: 65%
“…Allergenic proteins in raw and all processed snail extracts were determined by immunoblotting tests as explained previously 11 . In brief, protein bands after SDS‐PAGE were electrophoretically transferred onto a nitrocellulose membrane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Asian region, especially Southeast Asia, the Suction Snail (Cerithidea obtusa) is processed into delicious food and as a raw material for medicines. In Indonesia, the sucking snail (Cerithidea obtusa) is used as a traditional medicine to treat several diseases including fever, sores and itching (Misnan et al, 2016) (Kamaruddin et al, 2017) (Natalia et al, 2022). Suction snail (Cerithidea obtusa) besides being consumed by the public, it is also sold in the market because it has a fairly high price.…”
Section: Introductionmentioning
confidence: 99%
“…At the Muara Angke fish market, the stock of this species is rare and must compete with buyers who send it to Taiwan or Singapore (Purwaningsih, 2012). Likewise in Malaysia, Cerithidea obtusa has a high market demand and is popular among the local population (Misnan et al, 2016) (Chaterine Yolandika, 2022) (Nuni Anggraini, Yolandika, et al, 2022) (Utoyo et al, 2018)(Clara Yolandika et al, 2021. In Tanah Merah Sub-district, apart from being sold in local or regional markets, in January 2019 the Suction Snail (Cerithidea obtusa) was officially exported to Malaysia as much as 12.5 tons).…”
Section: Introductionmentioning
confidence: 99%